Effect of different tool pin diameter on mechanical properties of friction stirred welded AISI 304 stainless steel plate. (2021) - Kr Singh, Dilip; Sengupta, Kaushik; Karmakar, Souvik; Mondal, Arpan K.; Bose, D.
Abstract: The investigations was carried out to investigate the effect of different friction stir tool pin diameter on mechanical, microstructural properties and welding efficiency of the Stainless Steel AISI 304 friction stir welded specimen. The experiment were carried out at constant tool rotating speed of 1050 rpm, welding speed of 24 mm/min and tools with diameter ranging from 2.5 mm to 4.9 mm at 0.3 mm increasing value. The constant axial force of 10 KN has been applied to perform the friction stir joining. The welded specimens were inspected microscopically and analyzed to obtained mechanical properties such as hardness and UTS, as per the ASTM standard. The maximum tensile strength has been observed as 504 MPa at 2.8 mm tool pin diameter. The maximum welding efficiency of 99% has been observed. The lower tensile strength of the other joints found were due to lower and non-uniform heat distribution at the surface. The microstructure of welded specimen has been analyzed and characterized at different zones by using an optical microscope.